(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
The seabed generally has varying relief or topography from the land boundary to the seabed. However, this amazing topography sometimes does not make a meaningful impression for many people, because its shape cannot be seen directly (Nontji, 1987). The picture of the bottom of the waters can be known by measuring the depth of the sea. This research was carried out to measure and describe the basic morphometry of Sulamadaha coastal waters. This research was carried out for 1 month. Water depth measurements are carried out using an acoustic instrument (Fish-Finder) which is carried out on a boat (ship) while sounding. The tool used in this research is the Garmin 350 C type using dual frequency (50 Hz and 200 Hz). Reading and recording of the position (Latitude and Longitude) and water depth is carried out at any precise time (fix point). Next, the results obtained are recorded on the prepared data entry sheet. The data obtained was then processed using the Microsoft Excel application program, Surfer 10 program, and ArcGIS 10.1 program. Based on the results of data processing and analysis, a water depth value of no more than 110 m was obtained. The level of beach morphometry obtained from a number of profiles based on differences in depth contours shows slope values varying between 2.6% - 79.5% which are classified from flat slopes to very steep slopes.